Serious game in the training of nurses regarding peripherally inserted central catheter management (Research, Society and Development, 2022)
Objective: To identify, in the scientific evidence, the domains and interaction designs of serious games as a technological innovation in the training of nurses regarding the handling of the peripherally inserted central catheter. Method: Review of the LILACS, SCIENCE DIRECT, MEDLINE, CINAHL and COCHRANE databases whose descriptors central venous catheterization, peripheral venous catheterization, nursing students and experimental games were part of timeless, complete and free publications. The search resulted in 344 publications. After eligibility criteria, 11 composed the final sample. Results: Articles were categorized according to pedagogical objectives: to promote awareness and behavior change; develop clinical reasoning and decision-making skills; and improve theoretical-practical knowledge. Conclusion: The use of serious games for nursing students accommodates multiple educational domains that propose: interaction design with questions and answers, 3D virtual immersion or thematic rooms. Although in Brazil the peripherally inserted central catheter is configured as the only central line vascular device whose implantation can be performed by qualified nurses, given the gap in the findings, there is still a need to develop technologies for its process of teaching-learning. Thus, it is expected to encourage an interest in innovative technologies in domains not yet addressed in nurse educators.